Real-time fMRI neurofeedback reduces auditory hallucinations and modulates resting state connectivity of involved brain regions: Part 2: Default mode network -preliminary evidence. (February 2020) - Bauer, Clemens C.C.; Okano, Kana; Ghosh, Satrajit S.; Lee, Yoon Ji; Melero, Helena; Angeles, Carlo de los; Nestor, Paul G.; del Re, Elisabetta C.; Northoff, Georg; Niznikiewicz, Margaret A.; Whitfield-Gabrieli, Susan
Highlights: A single session of real-time fMRI neurofeedback targeting default mode network (DMN) significantly increased its anticorrelations post neurofeedback. DMN targeted neurofeedback resulted in reduced severity of auditory hallucinations (AHs) in patients with pharmacology-resistant AHs. There was a significant correlation between the increase in DMN - superior temporal gyrus connectivity and the reduction in AHs scores post neurofeedback. Abstract: Auditory hallucinations (AHs) are one of the most distressing symptoms of schizophrenia (SZ) and are often resistant to medication. Imaging studies of individuals with SZ show hyperactivation of the default mode network (DMN) and the superior temporal gyrus (STG). Studies in SZ show DMN hyperconnectivity and reduced anticorrelation between DMN and the central executive network (CEN). DMN hyperconnectivity has been associated with positive symptoms such as AHs while reduced DMN anticorrelations with cognitive impairment. Using real-time fMRI neurofeedback (rt-fMRI-NFB) we trained SZ patients to modulate DMN and CEN networks. Meditation is effective in reducing AHs in SZ and to modulate brain network integration and increase DMN anticorrelations. Consequently, patients were provided with meditation strategies to enhance their abilities to modulate DMN/CEN. Results show a reduction of DMN hyperconnectivity and increase in DMNCEN anticorrelation. Furthermore, the change in individual DMN connectivity significantly correlated with reductions in AHs. This is the first time that meditation enhanced through rt-fMRI-NFB is used to reduce AHs in SZ. Moreover, it provides the first empirical evidence for a direct causal relation between meditation enhanced rt-fMRI-NFB modulation of DMNCEN activity and post-intervention modulation of resting state networks ensuing in reductions in frequency and severity of AHs.